METHOD OF JUSTIFICATION OF OPERATIONAL PARAMETERS OF VIBRATING ROLLERS FOR COMPACTION - S. V. Saveliev; I. K. Poteryaev; G. G. Buriy; A. S. Beloded (Вестник СибАДИ)
This article investigated the frequency of the oscillation exciter during compaction of soil embankments recommended for vibratory rollers «Raskat». The technique justification regime parameters of vibrating rollers for soil compaction. A program to automate the process of the operation mode for a particular model of vibratory roller with compaction of different soil types. The research will improve the performance and efficiency of the use of vibratory rollers for soil compaction.